Good News for Some Banks - Renée B. Adams (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2021)
Bankers are directors of Federal Reserve Banks. I document that a) banker directors of the New York Fed attend more meetings about the financial sector; b) elections for Reserve Bank directorships are more contested for bankers, but less so for large banks and American Banking Association directors; d) the market reaction to bankers' elections to Reserve Bank boards is 1%; e) the market reaction to insider purchases is 1.3% higher when banker directors are on a Reserve Bank board; f) Fed enforcement actions appear more moderate for banker directors. Reserve Bank directorships appear to be good news for some banks.
Keywords: E58; G28; G30; 330; Federal Reserve; Director; Banks; Conflicts of Interest; Political Connection; Reputation; Insider Trading; Enforcement Actions; Regulatory Capture